Evaluasi Usability Aplikasi Sibersih UP3 Jambi Menggunakan System Usability Scale (SUS) - Refriansyah, Evan (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2025)
Digital transformation in public services encourages the development of internal information systems, such as the SIBERSIH application by PT. PLN (Persero) UP3 Jambi, which functions to record, report, and monitor the cleanliness of workspaces. The success of an application is not only determined by its features and technology, but also by its usability—how easy, efficient, and satisfying it is to use. Therefore, an initial usability evaluation of the SIBERSIH application was conducted using the System Usability Scale (SUS) method, which offers a simple and effective solution. This study contributes by providing an initial measurement of the usability quality of the SIBERSIH application based on direct experiences from early users. The method used in this study is the System Usability Scale (SUS), which consists of 10 questionnaire items with responses using a 5-point Likert scale. A total of 12 cleaning staff members were involved as early users. The data collected were analyzed using the standard SUS calculation formula. The evaluation results showed an average SUS score of 86.87. This score places the SIBERSIH application in the "acceptable" category within the acceptability range, receives a grade scale of B, and has an adjective rating of “excellent.” This means the application is considered very good and easy to use by non-technical users. This assessment indicates that the application meets the aspects of ease, convenience, and user satisfaction. In conclusion, the SIBERSIH application has a high usability rating and is well-received by early users. This evaluation provides a strong foundation for further development of the application to better support office cleanliness services.